Brand Awareness and Its Impact on Purchase Decisions for K-Pop Merchandise on Weverse Shop - Hasanah, Hajar Sri; Koeswandi, Tika; Rachmani, Nizza Nadya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to determine the effect of brand awareness on K-pop merchandise purchases made through the Weverse Shop application. The study employs a quantitative approach by distributing online questionnaires. This study uses primary data as its data source. The study population consisted of Indonesian K-pop fans who were familiar with and had access to the Weverse Shop application. A total of 100 people were surveyed. The analysis techniques included validity and reliability tests, simple linear regression, t-tests, and the coefficient of determination (R²). The results show that brand awareness significantly influences purchasing decisions. Regression analysis proves that brand awareness positively affects purchasing decisions; the greater a consumer's awareness of a brand (in this case, Weverse Shop), the greater their tendency to purchase merchandise through that platform.